The exclusive breastfeeding experiences of working mothers in West Sumatera (Sumbar) Peduli ASI community - Sari, Yanti P.; S., Yosi; V., Nella (International Journal of Research in Medical Sciences, 2017)
Background: Exclusive Breast feeding is one of the world wide programs to prevent a baby from any kind of disease and improve their immunity. Various health promotion efforts are always made to keep this program succeed. However, the result of the surveys in Indonesia showed the achievement of the exclusive breastfeeding is remains low. The aim of this study is to explore the experience of a working mother who succeeded to give exclusive breastfeeding. Methods: This research used qualitative study with phenomenological approach. Four participants were chosen from “Sumbar Peduli ASI Community” by purposive sampling technic. Data was collected by in-depth interview. Data analyzed used Collaizi method. Results: Based on the data analysis, it was found three themes, that are “the sacrifice of a working mothers to give exclusive breastfeeding”, “provided a good support system” and “encountered problems” and seven sub-themes, that is “sacrifice time”, “physical sacrifice”, “family support”, “social support”, “health workers support”, “technical problems” and “non-technical problems”. Conclusions: To be successful in providing exclusive breastfeeding, mothers have to sacrifice time and physically, to get the support of family, social and health workers so that obstacles can be solved.